1991
DOI: 10.1063/1.348459
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport analysis by electron-beam-induced current at variable energy of thin-film amorphous semiconductors

Abstract: Decay of the electronbeaminduced current in hydrogenated amorphous silicon devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The electron hole recombination can in turn break Si-H bonds to produce mobile H and DBs (dangling bonds). 27 While traversing the matrix, the b particles lose energy rapidly with depth and the effective active depth for electrons with energy of $5.7 keV is around 50 nm in a-Si:H. 28 Within this depth, extra DBs will be created and provide for the hydrogen (tritium) accommodation. This is consistent with the tritium depth observed in Fig.…”
Section: A Tritium Solubilitymentioning
confidence: 99%
“…The electron hole recombination can in turn break Si-H bonds to produce mobile H and DBs (dangling bonds). 27 While traversing the matrix, the b particles lose energy rapidly with depth and the effective active depth for electrons with energy of $5.7 keV is around 50 nm in a-Si:H. 28 Within this depth, extra DBs will be created and provide for the hydrogen (tritium) accommodation. This is consistent with the tritium depth observed in Fig.…”
Section: A Tritium Solubilitymentioning
confidence: 99%
“…Takahama et al [1] and Fischer [2] have calculated PDICE for amorphous silicon (aSi:H) PIN solar cells using QE experiments. Electron beam-induced current (EBIC) technique at variable electron beam energy has also been used to calculate PDICE [3]. In these methods PDICE at 'm' grid points in the device, must be calculated using the measured QE's at 'n' photon wavelengths or electron beam energies, using matrix inversion.…”
Section: Introductionmentioning
confidence: 99%
“…In crystalline materials the electron beam induced current technique (EBIC) has been largely applied either to qualitatively study defects, grain boundary, depletion, and inversion layer as was reported by Lander et al (1963) and MacDonald and Everhart (1965) or to quantitatively investigate transport properties leading to the determination of diffusion length, surface recombination velocity, and lifetime as was reported by Wittry and Keyser (1965), Wu and Wittry (19781, and Leamy (1982). In amorphous silicon, one can expect to derive information from EBIC measurements such as the depth collection profile (Najar et al, 1991), the potential or field distribution, and hopefully the density of gap states (Rajopadhye et al, 1988) and other transport parameters. In these approaches, some calculation parameters need to be known, such as the mean electron hole pair creation energy, the electron energy range, and the electron generation function.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are generally known in crystalline silicon although some discrepancies exist between measurements (Bresse, 1972). In amorphous silicon, a preliminary study, using both the well known Everhart-Hoff generation function (Everhart and Hoff, 1971) and a Monte-Carlo generation function (Napchan and Hold, 1987), was performed by Najar et al (1991). It was, however, observed that this method is extremely sensitive to the choice of the electron generation function.…”
Section: Introductionmentioning
confidence: 99%